2020
DOI: 10.3892/ijo.2020.5103
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DNA‑PK by gefitinib causes synergism between gefitinib and cisplatin in NSCLC

Abstract: Lung cancer has the highest incidence and mortality rates among the malignant tumor types worldwide. Platinum-based chemotherapy is the main treatment for advanced non-small-cell lung cancer (NSCLC), and epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) have greatly improved the survival of patients with EGFR-sensitive mutations. However, there is no standard therapy for treating patients who are EGFR-TKI resistant. Combining EGFR-TKIs and platinum-based chemotherapy is the most popular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…AZD7648, a highly-potent and specific DNA-PK inhibitor, sensitized the anti-NSCLC cell activity by radiation, chemotherapy and olaparib [ 36 ]. Pan et al, have shown that gefitinib could selectively inhibit EGFR and decrease DNA-PK activity, thereby enhancing cytotoxicity by cisplatin against NSCLC cells [ 37 ]. Liang et al, reported that DNA-PK inhibition could sensitize NSCLC cells to a third-generation EGFR blocker osimertinib [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…AZD7648, a highly-potent and specific DNA-PK inhibitor, sensitized the anti-NSCLC cell activity by radiation, chemotherapy and olaparib [ 36 ]. Pan et al, have shown that gefitinib could selectively inhibit EGFR and decrease DNA-PK activity, thereby enhancing cytotoxicity by cisplatin against NSCLC cells [ 37 ]. Liang et al, reported that DNA-PK inhibition could sensitize NSCLC cells to a third-generation EGFR blocker osimertinib [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the widespread resistance to cisplatin renders malignant cells less susceptible to the antiproliferative and cytotoxic effects of the drug [2]. Through combination with third generation cytotoxic agents such as gemcitabine, taxanes or ge tinib could signi cantly improve the curative effect of cisplatin, however, these cytotoxic drugs are often associated with severe side effects, and their clinical applications are limited seriously [3][4][5]. Therefore, it is urgent to nd adjuvant drugs which can be used in combination with cisplatin, enhance its e cacy, and decrease its side effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Gefitinib, which is one of the epidermal growth factor receptor (EGFR) small molecule tyrosine kinase inhibitor tyrosine kinase inhibitors (TKIs), is widely used for patients with non-small cell lung cancer (NSCLC) harboring EGFR mutations 20 , including exon 19 deletion and exon 21 L858R mutation. However, numerous patients cannot benefit or continue to benefit from EGFR-TKI monotherapy due to primary and secondary drug resistance after a period of treatment 21 . CSCs were found enriched and the EGFR mutant cells acquired resistance during the treatment with EGFR inhibitors 22 .…”
Section: Introductionmentioning
confidence: 99%